The new principal's fieldbook : strategies for success - Robbins, Pamela; Alvy, Harvey B. (ASCD, Association for Supervision and Curriculum Development, 2004)
Grounded in recent research and successful practice, The New Principal's Fieldbook prepares new and aspiring principals for the unexpected twists and turns of school leadership. Capitalizing on their experiences and those of other educational leaders, authors Pam Robbins and Harvey Alvy offer practical information, research-based strategies, and provocative stories to help principals develop into visionary leaders skilled in promoting the success of students and teachers. Surprises, obstacles, and opportunities characterize the leadership path. Within the chapters, the authors use research and specific examples from recognized practitioners to create a road map for navigating the complex challenges of the principalship. Collectively, the book's themes mirror key content areas addressed by the ISLLC Standards for School Leaders as well as other topics essential for success: Creating a shared vision that places student learning at the heart of the school; Transforming toxic cultures into positive cultures; Dealing with challenging experiences unique to new principals; Promoting quality teaching and learning; Creating professional learning communities; Facilitating change within the school culture; Building productive partnerships with central office staff, parents, and the greater community; Designing management tasks as leadership tools; Working with unions, budgets, the law, and the media; Balancing personal and professional responsibilities; Leading ethically and with emotional intelligence. Robbins and Alvy guide the reader through important concepts and practices, including instructional leadership, data-driven decision making, differentiated supervision, professional development, crisis intervention, and time management. At the end of each chapter, they invite readers to reflect on how to apply their new knowledge to real situations. Covering everything from everyday management tasks to the larger goal of student success, The New Principal's Fieldbook is an essential guide for new and aspiring principals.